PENGARUH LATIHAN BENCH DIP TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA PEMAIN TERATAI TENNIS CLUB PEKANBARU - Subroto, M.Imron Subroto; Juita, Ardiah Juita; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract, This research conducted to determine whether there is any influence bench dip exercise on the arm and shoulder muscles power for Teratai Tennis Club Pekanbaru, so when the players do forehand technic they get maximum results. Themethod ofthis research is experimental treatment (Experimental research), with in this research Teratai Tennis Club Pekanbaru.This population in this research is the players of Teratai Tennis Club Pekanbaru and the sample is a 6 members. Expanding dynamometer test as the instrument, which is designed to measure the strength of the arm and shoulder muscles. Then the data is processed with statistics, lilifors test with 0,05α significant level for normality test. The influence of bench dip exercise on arm and shoulder muscles strength as the hyphothesis. Based on the T analysis produces TTest at 22.24 and TTable 2.015 means TTest> TTable. Based on the analysis of statistical data, 17.50 is the average of Pree-test and 22.17 the average post-test. So, the data is normal. In conclusion, there is any influence of Bench Dip exercise on the arm and shoulder muscles strength for Teratai TennisClub Pekanbaru. Keywords: Bench Dip, arm and shoulder muscles strength.